Rancang Bangun Program menggunakan MetodeFuzzyuntukPenilaian Aspek Palemahan pada Sistem Subak(Studi Kasus pada Sistem Subak di Kawasan Warisan Budaya DuniaCatur Angga Batukau) - Kadek Dwi Ananda Nugraha; Sumiyati Sumiyati; I Putu Gede Budisanjaya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
Subak is an institution in charge of regulating the irrigation traditionally. System Subak activities are based on Tri Hita Karana (THK). One aspect of Tri Hita Karana (THK) is the palemahan aspect. The purpose of this research was to develop a program to assess the condition of palemahan aspect in subak system using Matlab-GUI based fuzzy logic that named TAKSU Information System (Tri Hita Karana Subak). In creating a fuzzy toolbox, the most important step to do is to design rules. Data were collected by survey method, direct observation and measurement. The data were categorized by value and then analyzed with fuzzy logic. Subak were assessed by using three value criteria that were Good = 3, Medium = 2, Less = 1. This program consists of input, an algorithm which is a function of the design carried out on the fuzzy Matlab toolbox and output as a result of the program. Based on the results of the validation carried out on two samples of subak, the value of Subat Jatiluwih was 2.23 with the criteria of Good and Subak Puring was 2.73 with the criteria of Good. These results indicate that this program can operate properly.